2020
DOI: 10.21608/ejbo.2020.21728.1424
|View full text |Cite
|
Sign up to set email alerts
|

Illustration and Description of the Recent Bryaceae Records from Bahariya Oasis ─ Egypt

Abstract: T WO species of Bryaceae are recent records for the bryoflora of Egypt from Bahariya Oasis (Western Desert): Bryum klinggraeffi Schimp. and B. valparaisense Thér. In addition, Bryum dichotomum Hedw. is recorded for the first time from the study area. Thus the number of mosses known from Egypt becomes188 and from Bahariya oasis 14. The two recently recorded species are described and illustrated and details are given of the collection sites and habitats. Notes are also given on their wider distributions along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Then In 1972, Imam and Ghabbour published the first alphabetical list of mosses with 69 taxa, followed by another list by El-Saadawi and Badawi (1977). After that, the work has continued until now with recording 201 moss taxa (El-Saadawi et al, 2015;Hassan et al, 2017;El-Sakaty et al, 2018;Khalil and Farag 2018;Taha 2020;Abou-Salama et al, 2021;Lashin et al, 2022;Isaak et al, 2023). The old records from 1812 to 1966 were not present in the CAIA herbarium section Bryophyta, which was founded in 1972 (Vitt et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Then In 1972, Imam and Ghabbour published the first alphabetical list of mosses with 69 taxa, followed by another list by El-Saadawi and Badawi (1977). After that, the work has continued until now with recording 201 moss taxa (El-Saadawi et al, 2015;Hassan et al, 2017;El-Sakaty et al, 2018;Khalil and Farag 2018;Taha 2020;Abou-Salama et al, 2021;Lashin et al, 2022;Isaak et al, 2023). The old records from 1812 to 1966 were not present in the CAIA herbarium section Bryophyta, which was founded in 1972 (Vitt et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Among the bryophytes, mosses are the most diverse in terms of species richness (Crandall-Stotler & Bartholomew-Began, 2007), with about 12,000 (Vanderpoorten & Goffinet, 2009) and 14,000 (Asakawa & Ludwiczuk, 2017;Das et al, 2022) species worldwide. Moreover, bryophytes are ubiquitous plants (Hodgetts et al, 2019) that can occupy a variety of habitats (Crandall-Stotler & Bartholomew-Began, 2007;Budke et al, 2018;Taha, 2020;Dziwak et al, 2022) compared to vascular plants (Sabovljević et al, 2022). Due to their structure, bryophytes are very sensitive to environmental conditions (Sabovljević et al, 2022), which makes them good indicators for environmental changes (Hallingback & Hodgetts, 2000;Mishler, 2001;Das et al, 2022), especially the epiphytic bryophytes which are predictably sensitive to global warming because of their direct connection to atmospherical conditions (Gradstein, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Number of moss taxa now from Egypt has been quietly increased in the last decade into 188 taxa belonging to 59 genera, 17 families and 10 orders (El-Saadawi et al, 2013 a,b;Ibrahim et al, 2013;Hassan et al, 2017;El-Sakaty et al, 2018;Khalil and Farag, 2018;Taha, 2020). The distribution of the 188 moss taxa in the 11 surveyed phytogeographical territories of Egypt (out of 13 territories) showed that Southern Sinai, Western Mediterranean Costal Land, Cairo, and Isthmic Desert of Egypt are the richest territories regarding the number of recorded moss taxa (El-Saadawi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%